A novel low-volume two-chamber microfabricated platform for evaluating drug metabolism and toxicity - Bale, Shyam Sundhar (Technology (Singap World Sci), 2015)
To evaluate drug and metabolite efficacy on a target organ, it is essential to include metabolic function of hepatocytes, and to evaluate metabolite influence on both hepatocytes and the target of interest. Herein, we have developed a two-chamber microfabricated device separated by a membrane enabling communication between hepatocytes and cancer cells. The microscale environment created enables cell co-culture in a low media-to-cell ratio leading to higher metabolite formation and rapid accumulation, which is lost in traditional plate cultures or other interconnected models due to higher culture volumes. We demonstrate the efficacy of this system by metabolism of tegafur by hepatocytes resulting in cancer cell toxicity.